The production of the professional master's degree in nursing of the Federal University of Santa Catarina, 2013-2016 - Cláudio José de Souza; Zenith Rosa Silvino
ABSTRACT Objective: To summarize the production of the Professional Master's Program in Nursing Care Management of the Federal University of Santa Catarina, between 2013 and 2016. Method: electronic documental research. After data collection, we analyzed the numbers of defenses in relation to what was predicted by the respective public notices; as well as sex, training time and professional area of the authors; scenario, context and research line; general objective, analysis support model, methodological approach, instruments/techniques of data collection, and technique of analysis; and, finally, technological productions. Results: 57 dissertations were found and subjected to analysis. The highest number of defenses took place in 2016, in the public scenario, in a care context, with a qualitative approach and having assistance protocols as a final product. Conclusion: Although the country has weaknesses in its educational system, results of the post-graduate level stand out through the technological productions of professional master's studies in nursing.